HUBUNGAN KEKUATAN KELUARGA DENGAN PERILAKU SEKSUAL BERESIKO PADA REMAJA DI KELURAHAN BAILANG LINGKUNGAN V KECEMATAN BUNAKEN KOTA MANADO - Sunarti Arsad; Bayu Dwisetyo; Nurlela Hi.Baco (Jurnal Rumpun Ilmu Kesehatan, 2022)
Adolescents are residents aged 10-18 years, while according to the Population and Family Planning Family strength is one of the most important things in preventing the occurrence of risky sexual in adolescents. The purpose of this study is to find out the relationship of family strength to sexual behavior at risk in adolescents of environmental bailang village v. This study was conducted in the early teens of bailang lingungan v village, Population of 130 respondents with a sample number of 33 resonden. This was done in August. This type of research is research using descriptive analytical methods that are cross sectional. The sampling technique uses purposive sampling. Data collection using the processor then collected data and analyzed using the Chi-Square test with a α level (≤ 0.05. Test This means that there is a significant relationship between family strength relationships and risky sexual behavior in. adolescents in the neighborhood. The conclusion of this study is that there is a family strength relationship with sexual behavior at risk in adolescents in the neighborhood. Advice the results of this study for developments in the field of nursing in the future.